Guía psicoeducativa basada en arteterapia para mejorar las habilidades sociales de los estudiantes de octavo año de educación básica paralelo a, de la unidad educativa Manuel Cabrera Lozano, 2019-2020. - Montoya Ordoñez, Glenda Alexandra (2020)
The social skills shortfall inflicts issues in the cognitive, emotional, social and learning development. Therefore, a research entitled: PSYCHOEDUCATIONAL GUIDE BASED ON ART THERAPY TO IMPROVE THE SOCIAL SKILLS AMONG STUDENTS OF EIGHT YEAR OF BASIC EDUCATION PARALLEL A, AT UNIDAD EDUCATIVA MANUEL CABRERA LOZANO; 2019-2020, was carried out; the general aim was to implement a psychoeducational guide based on art therapy to improve the social skills among these students. It was a cross sectional, quasi-experimental designed, descriptive research; the methods used were: scientific, deductive, analytical, modelling and the Pearson’s linear correction coefficient statistical method (r). The Goldstein Social Skills scale was applied among 23 students, between 11 and 13 years of age. It was found in the previous results (pre-test) where they evidenced the existence of deficits in the different areas of social skills: 18.18% in advanced social skills; 24.39% in skills related to feelings; 34.21% in alternative skills to aggression; 28.21% in skills to cope with stress and 25% in planning skills. After the intervention (post-test) it was observed that 84.38% improved advanced social skills, 78.69% skills related to feelings, 57.69% alternative skills to aggression, 67.92 % in skills to cope with stress and 63.46% in planning skills. To conclude, the psychoeducational guide founded on art therapy techniques achieve a value of r=0.61 moderately positive in the Pearson’s linear correlation scale, providing meaningfulness to the enhancement of social skills, thus validating the intervention proposal.